Persistence of influenza on surfaces. Issue 2 (February 2017) - Thompson, K.-A.; Bennett, A.M.
Summary: Background: Close contact transmission (either direct or large droplet/droplet nuclei) is considered the main driver of influenza outbreaks but there is limited information regarding the role of fomites in transmission. Aim: To investigate the surface stability of influenza strains and thereby the role of fomites in transmission. Methods: The viability and quantitative reverse transcription–polymerase chain reaction (qt-RT–PCR) signal of five influenza strains (A/PR/8/34/H1N1, A/Cal/7/09/H1N1, A/Cal/4/09/H1N1, A/Sol/54/06/H1N1, and A/Bris/59/07/H1N1) seeded on to three surfaces (cotton, microfibre, and stainless steel) were assessed over time. Coupons of material were seeded with 10 μL of a 10 6 –10 8 pfu/mL suspension of cell culture-derived virus stock supplemented with 0.3% bovine serum albumin. Coupons were assayed by plaque assay and qt-RT–PCR at 1, 24 h, and weekly for seven weeks using a vortex-mixing elution method. Findings: Viable virus was detected from coupons for up to two weeks (stainless steel) and one week (cotton and microfibre), whereas detection of viruses by PCR was made for the entire seven-week study period. No strain differences were found. Ninety-nine percent reduction values (as a function of the seeding stock) were determined to be 17.7 h for cotton ( R 2 = 0.86), 34.3 h for microfibre ( R 2 = 0.80), and 174.9 h for stainless steel ( R 2 = 0.98). Conclusion: Viable influenza was recovered from surfaces for up to two weeks. By contrast, influenza could be detected by PCR for more than seven weeks. These results have important implications for determining infection control protocols, cleaning regimes and sampling methods in healthcare settings.